EMT, Stemness and Tumor Plasticity in Aggressive Variant Neuroendocrine Prostate Cancers - Soundararajan, Rama (Biochim Biophys Acta Rev Cancer, 2018)
Neuroendocrine/Aggressive Variant Prostate Cancers are lethal variants of the disease, with an aggressive clinical course and very short responses to conventional therapy. The age-adjusted incidence rate for this tumor sub-type has steadily increased over the past 20 years in the United States, with no reduction in the associated mortality rate. The molecular networks fueling its emergence and sustenance are still obscure; however, many factors have been associated with the onset and progression of neuroendocrine differentiation in clinically typical adenocarcinomas including loss of androgen-receptor expression and/or signaling, conventional therapy, and dysregulated cytokine function. “Tumor-plasticity” and the ability to dedifferentiate into alternate cell lineages are central to this process. Epithelial-to-mesenchymal (EMT) signaling pathways are major promoters of stem-cell properties in prostate tumor cells. In this review, we examine the contributions of EMT-induced cellular-plasticity and stem-cell signaling pathways to the progression of Neuroendocrine/Aggressive Variant Prostate Cancers in the light of potential therapeutic opportunities.